The Principles of the Consumer Right Protection in Electronic Trade: A Comparative Law Analysis - Kirillova, Elena Anatolyevna; Shergunova, Elena Anatolyevna; Ustinovich, Elena Stepanovna; Nadezhin, Nikolay Nikolaevich; Sitdikova, Lyubov Borisovna (International Journal of Economics and Financial Issues, 2016)
This paper investigates the specifics of electronic trade and the issues of protecting the rights of online-consumers, considers their rights and obligations, since we all face a radically new phenomenon in the sphere of trade – an unprecedented boom of electronic trade (e-commerce), based on the use of the Internet for concluding transactions and operations in the systems of wholesale and retail trade. The means of electronic communication provide broad opportunities for direct contacts between individuals from different countries. The development of electronic communications poses new tasks before the system of international private law, and one of them is the protection of the consumer rights, when conducting electronic trade. The main goal of this research is to explore the contemporary state of electronic trade worldwide and to outline the principles of the online consumer protection. Writing this paper, the following scientific methods were employed: the method of collecting and examining individual facts, of generalizing, of abstract scientific conceptualization, the methods of discovering the general rule. As a result of the analysis conducted, we can present a list of the basic principles of protecting the rights of the online consumers – the principle of the right to return the goods bought via the Internet; the right to address complaints, when buying goods via the Internet; the principle of recognition of online contracts; the principle of providing effective protection; the principle of protecting the personal data of the online consumers. The paper suggests a definition of electronic trade by the authors. We conclude that it is necessary to devise an efficient structure for the judicial system, as well as the legislation that would be really applicable, in the implementation of the consumer right protection in electronic trade. Keywords: buyers; business operators; electronic trade, principles; transaction. JEL Classifications: D18, L81